ระบบประเมินพัฒนาการด้านความรู้ความสามารถของพยาบาล งานการพยาบาลผ่าตัด โรงพยาบาลศิริราช - ปรีชาคุณ, เบญจมาศ; พิบูลย์, สุพักตร์; พิบูลย์, สุพักตร์ (Thai Journal of Nursing, 2016)
การวิจัยและพัฒนานี้มีวัตถุประสงค์เพื่อพัฒนา ระบบประเมินพัฒนาการด้านความรู้ความสามารถของ พยาบาล งานการพยาบาลผ่าตัด โรงพยาบาลศิริราชและ ประเมินประสิทธิภาพของระบบฯที่พัฒนาขึ้น การดำเนิน การวิจัย มี 2 ระยะได้แก่ 1) พัฒนาระบบประเมินพัฒนา การด้านความรู้ความสามารถ กลุ่มตัวอย่าง เป็นพยาบาล วิชาชีพงานการพยาบาลสูติศาสตร์-นรีเวชวิทยา ที่ ปฏิบัติงานในห้องพักฟื้น จำนวน 19 คน และพยาบาล วิชาชีพงานการพยาบาลผ่าตัด จำนวน 20 คน และ 2) ประเมินประสิทธิภาพของระบบฯ ในสถานการณ์การปฏิบัติงานจริง กลุ่มตัวอย่างเป็นพยาบาลวิชาชีพงานการ พยาบาลผ่าตัดที่ปฏิบัติงานในห้องพักฟื้น จำนวน 33 คน พยาบาลวิชาชีพงานการพยาบาลผ่าตัด ที่เริ่มเข้าประจำการ จำนวน 20 คน และพยาบาลระดับบริหารงานการพยาบาล ผ่าตัด จำนวน 6 คน เลือกแบบเจาะจง เครื่องมือวิจัย ประกอบด้วยระบบประเมินพัฒนาการด้านความรู้ความ สามารถที่ใช้ระบบปฏิสัมพันธ์ผ่านเครือข่ายอินเทอร์เน็ต และแบบประเมินประสิทธิภาพของระบบ การวิเคราะห์ ข้อมูลใช้ค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบค่าที และการวิเคราะห์เนื้อหา ผลการวิจัย พบว่า 1) ระบบประเมินพัฒนาการด้านความรู้ ความสามารถของพยาบาล งานการพยาบาลผ่าตัด โรงพยาบาลศิริราชที่พัฒนาขึ้น มีองค์ประกอบสำคัญ คือ (1) ปัจจัยนำเข้า ประกอบด้วยกลุ่มเป้าหมายผู้รับการ ประเมิน เนื้อหาความรู้และทักษะด้านการดูแลผู้ป่วยหลัง ผ่าตัดในห้องพักฟื้นและโปรแกรมฐานข้อมูลผ่านระบบ เครือข่ายอินเทอร์เน็ต (2) กระบวนการ เริ่มด้วย การ ตรวจสอบฐานความรู้และทักษะ การให้ข้อมูลย้อนกลับ การสนับสนุนให้กลุ่มเป้าหมายวางแผนพัฒนาตนเอง การตรวจสอบพัฒนาการและการประเมินเพื่อรับรอง ความรู้ความสามารถ และ (3) ผลลัพธ์ที่คาดหวัง คือ พัฒนาการด้านความรู้ความสามารถของพยาบาลวิชาชีพ งานการพยาบาลผ่าตัด 2) ระบบประเมินที่พัฒนาขึ้น มีประสิทธิภาพตาม มาตรฐานด้านความเหมาะสม ความเป็นไปได้ และความ เป็นประโยชน์ในระดับมาก ด้านความถูกต้องของระบบ ระบบมีความถูกต้องสามารถจำแนกความแตกต่างด้าน ความรู้ความสามารถ ระหว่างพยาบาลวิชาชีพงานการ พยาบาลผ่าตัดที่มีประสบการณ์มากกว่า 1 ปี กับพยาบาล วิชาชีพใหม่ได้อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 Development of knowledge and skill growth evaluation system of Perioperative nurses, Division of Perioperative Nursing, Siriraj Hospital. Preechakoon, B., Pibool, S., & Prommapun, B. The objectives of this study were to develop a system for evaluation of knowledge and skill development of perioperative nurses, Division of Perioperative Nursing, Siriraj Hospital and to assess its efficiency. The first phase was to develop a system for evaluation of knowledge and skill development. The sample consisted of 19 professional nurses working in the post-anesthesia care unit, and 20 professional perioperative nurses. The second phase was to assess the efficiency of the developed system. The sample consisted of 33 professional perioperative nurses working in the post-anesthesia care unit, 20 new professional perioperative nurses, and 6 perioperative nurse administrators. The research instruments comprised a system for evaluation of knowledge and skill development employing the interaction system via the internet network, and a system efficiency assessment. Data were analyzed using the percentage, mean, standard deviation, t-test, and content analysis. The research findings revealed: 1) The developed system for evaluation of knowledge and skill development of perioperative nurses, Division of Perioperative Nursing, Siriraj Hospital composed of 3 components; (1) the input comprising the target group to be evaluated, the knowledge and skills on taking care of patients after the operation in the post anesthesia care unit; and the database program via the internet network. (2) the process comprising the appraisal of basic knowledge and skills, the provision of feedback information, the encouragement of the target group to plan for self-development, the development appraisal, and the evaluation for certifying knowledge and skills, and (3) the expected outcome which was the knowledge and skill development of perioperative nurses. 2) The developed evaluation system was highly efficient according to the standards of appropriateness, feasibility, and utility. The accuracy standard, the system could discriminate the knowledge and skills of professional perioperative nurses who had more than one year experience from the new professional perioperative nurses at p< .05.